Is financial speculation with agricultural commodities harmful or helpful? A literature review of current empirical research - Matthias Georg Will; Sören Prehn; Ingo Pies; Thomas Glauben (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2012)
This literature survey comprises 35 empirical studies published between 2010 and 2012 that analyze the influence of financial speculation on the markets for agricultural commodities. According to the current state of research, there is little supporting evidence that the recent increase in financial speculation has caused either a)of the price level, or (b) the price volatility in agricultural markets to rise. Rather, fundamental factors are responsible for this. Therefore, most papers are not in favor of, but against (c) erecting market barriers by regulation. Against this background, the public alarm, which claims that financial speculation has detrimental effects and should be forbidden, seems to be a false alarm. Those who are interested in fighting global hunger should take care of fundamental factors and take appropriate measures to keep supply in step with demand, which is likely to rise in the near future. – – Dieser Literaturüberblick wertet 35 Forschungsarbeiten aus, die zwischen 2010 und 2012 veröffentlicht wurden und den Einfluss der Finanzspekulation auf die Agrarrohstoffmärkte empirisch untersuchen: Gemäß aktuellem Erkenntnisstand spricht wenig für die Auffassung, dass die Zunahme der Finanzspekulation in den letzten Jahren (a) das Niveau bzw. (b) die Volatilität der Preise für Agrarrohstoffe hat ansteigen lassen. Hierfür waren vielmehr realwirtschaftliche Faktoren verantwortlich. Deshalb sind die wissenschaftlichen Studien mehrheitlich nicht dafür, sondern dagegen, (c) regulatorische Marktzutrittsbarrieren zu errichten. Insofern ist der zivilgesellschaftliche Alarm zur Finanzspekulation als Fehl-Alarm einzustufen: Wer den Hunger in der Welt wirksam bekämpfen will, muss realwirtschaftlich dafür Sorge tragen, dass das Angebot an Nahrungsmitteln mit der auf absehbare Zeit steigenden Nachfrage Schritt halten kann.
urn:nbn:de:gbv:3:2-17773
Keywords: D84; G12; G13; G14; Q13; Q18; 330; Financial speculation; futures market; agricultural commodities; regulation; position limits; transaction tax; volatility; price level; Finanzspekulation; Terminmarkt; Agrarrohstoffe; Regulierung; Positions-Limits; Transaktionssteuer; Volatilität; Preisniveau